Lifetime risk and health-care burden of diabetic ketoacidosis: A population-based study - Ebrahimi, Fahim; Kutz, Alexander; Christ, Emanuel Remigius; Szinnai, Gabor (Frontiers in Endocrinology, 2022)
Objective. Diabetic ketoacidosis (DKA) is a life-threatening complication of both type 1 and type 2 diabetes. We aimed to assess population-based rates, trends and outcomes of patients with DKA. Design and Methods. This is a nationwide cohort study using hospital discharge claims data from 2010 to 2018 in Switzerland. Incidence rates and in-hospital outcomes of DKA were analyzed throughout lifetime: children (0-9 years), adolescents (10-19 years), and adults (20-29, 30-59, and 60-90 years). Analyses were stratified for type of diabetes mellitus and sex. Results. In total, 5,544 hospitalizations with DKA were identified, of whom 3,847 were seen in patients with type 1 diabetes and 1´697 in type 2 diabetes. Incidence rates of DKA among patients with type 1 diabetes were highest during adolescence with 17.67 (girls) and 13.87 (boys) events per 100,000 person-years (incidence rate difference [IRD]: -3.80 [95% CI, -5.59 to -2.02]) and decreased with age in both sexes thereafter. Incidence rates of DKA in patients with type 2 diabetes were low up to an age of 40 years and rose to 5.26 (females) and 6.82 (males) per 100,000 person-years in adults aged 60-90 years. Diabetic ketoacidosis was associated with relevant health-care burden independent of age, sex, or type of diabetes. The population-based incidence rate of DKA increased over time from 7.22 per 100,000 person-years in 2010 to 9.49 per 100,000 person-years in 2018. Conclusions. In type 1 diabetes highest incidence rates of DKA hospitalizations were observed among adolescent females. In comparison, in patients type 2 diabetes the risk for DKA steadily increased with age with higher rates in adult males. Over the 9 year study period, incidence rates of hospitalizations with DKA were increasing irrespective of type of diabetes. DKA was associated with a high burden of disease reflected by high rates of intensive care unit admission, prolonged hospital stay and high mortality rates, especially in elderly.